2016
DOI: 10.1097/dcr.0000000000000613
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Local Excision After Neoadjuvant Therapy for Rectal Cancer: Are ypT0 Tumors the Limit?

Abstract: Local excision after neoadjuvant therapy should only be considered a curative treatment if complete pathological response is obtained. Given the high rate of local recurrence among incomplete responders, future studies should focus on predicting patients who will achieve complete pathological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 45 publications
1
42
1
1
Order By: Relevance
“…This group previously undertook a systematic review of local excision following neoadjuvant therapy for rectal cancer, which found that the outcomes of patients who obtained a complete pathological response (ypT0) were comparable to those achieved with radical surgery . If a complete pathological response was not obtained (≥ypT1) and the patient did not proceed to radical surgery, then local recurrence exceeded 20% and long‐term survival was decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group previously undertook a systematic review of local excision following neoadjuvant therapy for rectal cancer, which found that the outcomes of patients who obtained a complete pathological response (ypT0) were comparable to those achieved with radical surgery . If a complete pathological response was not obtained (≥ypT1) and the patient did not proceed to radical surgery, then local recurrence exceeded 20% and long‐term survival was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Careful patient selection and accurate preoperative radiological tumour assessment are therefore required to ensure that individuals benefit from the decreased morbidity associated with local excision, but not at the risk of compromising long-term oncological outcomes. This group previously undertook a systematic review of local excision following neoadjuvant therapy for rectal cancer, which found that the outcomes of patients who obtained a complete pathological response (ypT0) were comparable to those achieved with radical surgery [8]. If a complete pathological response was not obtained (≥ypT1) and the patient did not proceed to radical surgery, then local recurrence exceeded 20% and long-term survival was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review by our own group suggested that local excision after neoadjuvant therapy for rectal cancer should only be considered as curative, with an acceptable level of local control, if a pCR was obtained. Pooled local recurrence rates were significantly greater and median disease-free survival significantly lower among tumours staged as ypT1 or above compared to ypT0 tumours [20] . In this article we describe our approach to the management of early rectal cancer, its staging and our evidence-based rationale for the use of neoadjuvant and adjuvant therapies.…”
Section: Introductionmentioning
confidence: 83%
“…This compared favourably to results achieved with radical surgery in equivalent stage disease. Outcomes for ≥ ypT1 tumours were much worse with pooled local recurrence and disease-free survival of 22% and 68%, respectively [20] . Despite the obvious limitations of study heterogeneity and their retrospective nature, we conclude that local excision should only be considered as a definitive therapy if a pCR, i.e., ypT0, is obtained in the excision specimen.…”
Section: Treatment Strategymentioning
confidence: 99%
See 1 more Smart Citation